Keselamatan dalam Persimpangan Tafsir: Kritik Historis dan Refleksi Teologis atas Isu-Isu Soteriologi - Christian Bayu Marhendra (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2025)
The doctrine of salvation is one of the central teachings in Christianity. The entire message of the Gospel essentially proclaims salvation for sinners through the redemptive blood of Christ. However, throughout church history, differing interpretations of Scripture have led to theological disputes regarding this doctrine. Soteriological controversies notably emerged in the 4th century through the debate between Augustine and Pelagius, and continued during the Protestant Reformation initiated by Martin Luther. These debates intensified as followers of Calvinism and Arminianism defended their respective understandings of salvation. This study aims to examine the historical and theological dynamics of the doctrine of salvation. The research employs a qualitative descriptive method with a literature review approach. Data are collected through the analysis of theological literature, empirical sources, and previously published scholarly works related to soteriological issues. This study is expected to provide a comprehensive understanding of the development and debates surrounding the doctrine of salvation throughout church history.